Evridikine besede molka: Vergilijeva in Ovidijeva upodobitev Evridike - Adam, Alja (Monitor ISH, 2008)
A comparison of Virgil's interpretation of the Orpheus and Eurydice myth with Ovid's reveals that the younger author Ovid fully adopts Virgilćs portrayal of Eurydice. Like the woman created by Pygmalion, Eurydice is an invisible object representing the body which Orpheus, who stands on the side of the intellect, needs in order to complete and re-create it with his artist's imagination, thus transcending his own mortality. But Eurydice's liminal position is also a source of her hidden power, which is manifested in various ways - through Virgil's ambiguous narrator, Proteus, as well as through Ovid's mythological allusions.
Keywords: književnost; literature; grška mitologija; spol; woman; ženske; feminism; feminizem; filozofija kulture